The Integrated Role of Laboratory, Nursing, Radiology, Physiotherapy, and Public Health Professionals in Enhancing Healthcare Quality and Patient Safety - Alzubaidi, Sahar Abdullah; Albaker, Fodeh Omer; Al-Rashidi, Fatimah Mutab; Alshammari, Foziyya Sileiman Faiz; Almehrej, Abdulrahman Mohammed Abdulrahman; Baidas, Sireen Fawzi; Alshahrani, Samar Abdulqadir; Aljohani, Amal Mohammed; Alasmri, Moshabab Said; Musalli, Basem Saleh; Shehab, Fatimah Ali Hsaasn Al; Althagafi, Majed Atiah (Journal of Posthumanism, 2024)
Integrated healthcare teams consist of complementary professionals working together to improve patient care across the continuum of health services. Their common goal is to deliver safe, appropriate, and quality services to individuals. Figures on avoidable harm demonstrate a persistent need to strengthen integrated healthcare teams and efforts to mainstream quality and safety into education. An array of disciplines contribute to integrated healthcare teams, including but not limited to laboratory, nursing, radiology, physiotherapy, and public health. All health professionals have specific roles and responsibilities in the quality and safety domains, but these responsibilities differ. Common themes emerge in the application of quality and safety frameworks across the professional spectrum, and competencies are relevant to the teaching of quality and safety. One framework for concerted quality and safety efforts draws on the Plan-Do-Study-Act (PDSA) cycle, aligning with the triple aim of enhanced patient experience, improved population health, and reduced per-capita cost of care [1]. Mainstreaming quality and safety into practice requires integration into the quotidian work of every health professional. Laboratory, nursing, radiology, physiotherapy, and public health professionals comprise key stakeholders in integrated healthcare teams, contributing uniquely to collaborative efforts that enhance safety and quality. Health professionals have a fundamental duty to protect and promote the health of communities, patients, and populations. The integration of quality and safety into practice is underpinned by an ascribed set of responsibilities and a suite of skills. Quality improvement necessitates knowledge of interdependence—within a given specialty and across all disciplines involved in a particular patient journey—among other essential competencies. The terminology associated with quality and safety varies across disciplines, and the responsibility at stake also differs. Nonetheless, the diverse occupations share a commitment to the improvement of safety and quality in health services. Leaders are needed to coordinate integrated healthcare teams and ensure cooperation, mutual assistance, equitable contribution, and support for the diverse activities of professionals across the various health-related occupations. Effective leadership establishes a team identity, clarifies approaches for interprofessional work, and creates a sense of shared purpose. The establishment of leadership-and-governance structures points to a widespread recognition of the paramount importance of harmonious teamwork and collaboration to patient safety and the quality of services provided to the public.